Evaluating the effectiveness and cost-effectiveness of British Sign Language Improving Access to Psychological Therapies: an exploratory study - Alys Young; Katherine Rogers; Linda Davies; Mark Pilling; Karina Lovell; Steve Pilling; Rachel Belk; Gemma Shields; Claire Dodds; Malcolm Campbell; Catherine Nassimi-Green; Deborah Buck; et al. (National Institute for Health Research, 2017)
Background: Improving Access to Psychological Therapies (IAPT) is a National Institute for Health and Care Excellence-approved approach to intervention for depression and/or anxiety. This exploratory study sets the groundwork for comparing psychological therapies for Deaf sign language users experiencing anxiety and/or depression, delivered in British Sign Language (BSL) by a Deaf therapist with usual access through an interpreter within the IAPT national programme. Objectives: (1) To explore the following questions: (a) is BSL-IAPT more effective than standard IAPT for Deaf people with anxiety and/or depression? and (b) is any additional benefit from BSL-IAPT worth any additional cost to provide it? (2) To establish relevant BSL versions of assessment tools and methods to answer research questions (a) and (b). (3) To gauge the feasibility of a larger-scale definitive study and to inform its future design. Design: A mixed-methods exploratory study combing an economic model to synthesise data from multiple sources; a qualitative study of understanding and acceptability of randomisation and trial terminology; statistical determination of clinical cut-off points of standardised assessments in BSL; secondary data analysis of anonymised IAPT client records; realist inquiry incorporating interviews with service providers and survey results. Settings: IAPT service providers (NHS and private); the Deaf community. Participants: Deaf people who use BSL and who are clients of IAPT services (n = 502); healthy Deaf volunteers (n = 104); IAPT service providers (NHS and private) (n = 118). Interventions: IAPT at steps 2 and 3. Main outcome measures: Reliable recovery and reliable improvement defined by IAPT; Deaf community views on the acceptability of randomisation; BSL terminology for trial-related language; clinical cut-off measurements for the BSL versions of the Patient Health Questionnaire-9 items (PHQ-9) and the Generalised Anxiety Disorder-7 (GAD-7); a valid BSL version of the EuroQol-5 Dimensions five-level version (EQ-5D-5L); costs, quality-adjusted life-years and incremental cost-effectiveness ratios. Data sources: IAPT service provider anonymised records of the characteristics and clinical outcomes of Deaf BSL users of BSL-IAPT and of standard IAPT; published literature. Results: Randomisation may be acceptable to Deaf people who use IAPT if linguistic and cultural requirements are addressed. Specifications for effective information in BSL for recruitment have been established. A valid EQ-5D-5L in BSL has been produced. The clinical cut-off point for the GAD-7 BSL is 6 and for the PHQ-9 BSL is 8. No significant difference in rates of reliable recovery and reliable improvement between Deaf users of standard IAPT or BSL-IAPT has been found. Whether or not BSL-IAPT is more cost-effective than standard IAPT is uncertain. Limitations: The small number of participating standard IAPT services who have seen Deaf clients means that there is statistical uncertainty in the comparable clinical outcome result. Clinical cut-off scores have not been verified through gold standard clinical interview methodology. Limited data availability means that whether or not BSL-IAPT is more cost-effective than standard IAPT is uncertain. Conclusions: There is a lack of evidence to definitively compare reliable recovery and reliable improvement between Deaf users of standard IAPT and BSL-IAPT. Instrumentation and prerequisites for a larger-scale study have been established. Future work: A prospective observational study for definitive results is justified. Funding: The National Institute for Health Research Health Services and Delivery Research programme.